2017
DOI: 10.1371/journal.pone.0178898
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles of five farmed Brazilian freshwater fish species from different families

Abstract: The proximate composition and fatty acid (FA) profiles of five Brazilian freshwater fish species, namely Brycon cephalus (BC), Cichla ocellaris (CO), Prochilodus lineatus (PL), Leporinus friderici (LF) and Pseudoplatystoma corruscans (PCO), were investigated. CO and LF exhibited the highest (p < 0.05) moisture content, as well as one of the lowest (p < 0.05) lipid values, whereas BC presented the lowest (p < 0.05) moisture and, alongside PL, the highest (p < 0.05) lipid content. The predominant FAs in the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 44 publications
(110 reference statements)
2
40
2
1
Order By: Relevance
“…In contrast to IA and IT, higher HH values are considered more beneficial to human health. Among fish species analyzed, the IA values ranged from the lowest 0.56 in Sillago sihama to the highest 1. respectively) in this study were higher than those reported in other marine species [10,32,41]. The HH ratios ranged between 0.65 in Selaroidea leptolepis and 1.41 in Trypauchen vagina.…”
Section: Fatty Acid Profilescontrasting
confidence: 75%
See 3 more Smart Citations
“…In contrast to IA and IT, higher HH values are considered more beneficial to human health. Among fish species analyzed, the IA values ranged from the lowest 0.56 in Sillago sihama to the highest 1. respectively) in this study were higher than those reported in other marine species [10,32,41]. The HH ratios ranged between 0.65 in Selaroidea leptolepis and 1.41 in Trypauchen vagina.…”
Section: Fatty Acid Profilescontrasting
confidence: 75%
“…Stearic acid (C18:0), ranging from 3.63% to 9.96%, was the second most abundant fatty acid identified in all the fishes. Especially noted, the myristic acid (C14:0), which promote hypercholesterolemia, was detected at a relatively high concentration in the examined species compared with previous studies demonstrating a negative factor in their consumption [10,32]. As SFAs with odd carbon numbers, pentadecanoic acid (C15:0) and heptadecanoic acid (C17:0) were present in small levels.…”
Section: Fatty Acid Profilesmentioning
confidence: 61%
See 2 more Smart Citations
“…Fish meat is an excellent source of animal protein and polyunsaturated fatty acids (PUFA), which benefit human health (Rodrigues et al, 2017). Marine fish have a higher content of ω−3 long chain polyunsaturated fatty acids than freshwater fish (Huynh & Kitts, 2009), and sardines contain more PUFA than many other marine species (Mesías et al, 2015).…”
mentioning
confidence: 99%